2021
DOI: 10.1590/1517-8692202127022020_0067
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Injuries in Soccer Players – Mappingfoot: A Prospective Cohort Study

Abstract: Introduction: Although the positive effects of physical activity on global health are well documented, sports practice is associated with a greater risk of injury; in professional soccer in particular, the risk is substantial. Objective: The primary objective of this study was to investigate the incidence of injuries among male athletes competing in the regional soccer championship. The secondary objective was to determine the prevalence of injuries. Methods: In this prospective cohort study, level of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 30 publications
0
5
0
5
Order By: Relevance
“…Os estudos selecionados foram tabelados ( Tabela 1 ) 5 6 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 , considerando o nome do autor e ano de publicação, tipo de artigo, título, objetivo do estudo e achados.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Os estudos selecionados foram tabelados ( Tabela 1 ) 5 6 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 , considerando o nome do autor e ano de publicação, tipo de artigo, título, objetivo do estudo e achados.…”
Section: Resultsunclassified
“…Um estudo com atletas do sexo masculino que competem um torneio regional de futebol buscou investigar a incidência e prevalência de lesões e constatou que os membros inferiores são mais acometidos em relação às demais partes do corpo, representando um total de 86,9%. 6 Outro autor também obteve resultado semelhante em sua pesquisa, obtendo um total de 85,5% das lesões identificadas, acometidas na mesma região anatômica. 5 Os membros inferiores são mais requisitados neste esporte e, por este motivo, as lesões nessa área são mais frequentes.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…For example, it would be useful to analyse the running phase and the running speed at which injuries occur. In runners, it has been reported that hamstring injuries occur while the athletes are running near their maximal speed [82], but such information has been reported by only four studies here [50,[58][59][60], reporting high-intensity running without specifying the running speed. Furthermore, there is debate on whether running injuries occur during the early stance or the swing phase of running [80,83].…”
Section: Injury-inciting Activities For Specific Injury Locationsmentioning
confidence: 99%